Pengaruh Profitabilitas, Likuiditas, Ukuran, Pertumbuhan Terhadap Struktur Modal Industri Otomotif Di BEI - Ema Putra, Dwi; Wijaya Kesuma, I Ketut (E-Jurnal Manajemen, 2014)
The funding decision is important for the company as it concerns the extent of the use of debt as compared to the level of equity in the financing of investment. Companies must determine whether to use internal funds first or external funds to finance investment so getting an optimal capital structure that will minimize capital costs borne by the company. This study aims to determine the effect of profitability, liquidity, size and growth rate of the company's capital structure in the automotive industry in Indonesia Stock Exchange. Debt to equity ratio is used as a proxy of capital structure. A total of 13 companies sample of 17 total population was obtained by purposive sampling method. Based on multiple linear regression analysis showed that profitability and liquidity partially significant negative effect on the capital structure, firm size not significant effect on the capital structure, and the growth rate significant positive effect on the capital structure, and profitability, liquidity, firm size and growth rate simultaneously effect the capital structure. Keywords : capital structure, profitability, liquidity, firm size, firm growth rate